(untitled) (A Social Science and Entrepreneurship Journal, 2026)
This research was conducted to dig out the root causes of ineffectiveness of marketing strategies implemented in English Educational Tourism Village in Pare, Kediri Regency and find the recommendations for them, specifically post- pandemic context. This research used a qualitative descriptive method, then, analyzed using a fishbone diagram. The result depicted that English courses in Pare, Kediri did not well implement marketing strategies, specifically digitally. It was because of lacking knowledge and skills regarding business management, a lack of capital and lacking high-quality human resources. In general, researchers gave some recommendations for evaluating marketing strategies such as: 1) Implementing Segmenting, Targeting, and Positioning (STP) strategies, 2) Digitalizing marketing strategies 3) Gaining more capital, and 4) Upscaling human resource competencies.